Prawo do sądu a oddalenie oczywiście bezzasadnego powództwa w świetle projektu zmian z 27.11.2017 r. do Kodeksu postępowania cywilnego: [The right of access to court in the light of the dismissal of obviously unfounded action in the draft amendments of November 27, 2017 to the Code of Civil Procedure] (Studia Prawnicze / The Legal Studies, 2018)
Artykuł omawia propozycję zawartą w projekcie nowelizacji z 27.11.2017 r. do Kodeksu postępowania cywilnego, tj. wprowadzenie do postępowania cywilnego dopuszczalności oddalenia roszczenia jako oczywiście bezzasadnego na posiedzeniu niejawnym w aspekcie zapewnienia i realizacji prawa jednostki do sądu. Autorka stawia tezę, że w świetle projektowanego art. 1911 Kodeksu postępowania cywilnego o „oczywistej bezzasadności” w rozumieniu tego przepisu można mówić jedynie w sytuacji, w której roszczenie powoda nie jest znane prawu. W przeciwnym razie, tj. w przypadku zbyt szerokiego zrozumienia tej instytucji, oddalenie powództwa jako „oczywiście bezzasadnego” może prowadzić do naruszenia prawa jednostki do sądu w świetle art. 6 EKPC. The article discuss the proposal included in the draft amendment from 27.11.2017, such as introduction to the civil proceedings of the admissibility of dismissing the claim as obvious groundlessness at a closed session in the context of providing to a person the right to a court. The author puts forward the thesis that in the light of Article 1911 Code of Civil Procedure, the “obvious groundlessness” of an action is a state in which the claim made by the claimant is unknown to the law. Otherwise, i.e. in the case of a too wide understanding of this institution, the dismissal of the action may lead to violation of the right of the individual to court in the light of Article 6 ECHR.